PENGARUH TENAGA KERJA, MODAL, JEJARING DAN HARGA TERHADAP OMZET PENJUALAN UMKM KEDAI KOPI SUDIMORO, MALANG - Nadeak, Michael Enrico; Bahtiar Fitanto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The coffee shop business is also growing in almost all cities in Indonesia, including Malang. With the increasing number of coffee shops popping up in the Sudimoro area, competition in the coffee industry will become increasingly fierce. The aim of this research is to determine the influence of labor, capital, networks and prices on the sales turnover of Coffee Shop SMEs in the Sudimoro Area, Malang. This research is a quantitative research with a sample of 30 coffee shops in the Sudimoro area, Malang that meet the research criteria. The data used is a combination of primary data from interviews and secondary data from financial reports. The data was then analyzed using classical assumption tests and multiple linear regression with the help of SPSS 23 software. The research results show that labor and capital influence the sales turnover of Coffee Shop MSMEs in the Sudimoro Area, Malang. However, network and price do not affect the sales turnover of Coffee Shop SMEs in the Sudimoro Area, Malang.